Germplasm characterization, association and clustering for salinity and waterlogging tolerance in bread wheat (Triticum aestivum) - SINGH, GYANENDRA; KULSHRESHTHA, N; SINGH, B N; SETTER, TIM L; SINGH, M K; SAHARAN, M S; TYAGI, B S; VERMA, AJAY; SHARMA, INDU (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted for characterizing germplasm, estimating interrelationship of traits and clustering of wheat genotypes in five environments covering salinity, waterlogging and neutral soils using, 100 elite but diverse genotypes with eight checks of bread wheat (Triticum aestivum L.). These genotypes were planted under five distinct environments during rabi 2009-10 under augmented design in four blocks wherein each check was repeated twice. The genetic variance, correlation coefficients and cluster analysis were carried out for assessment of lines through seven metric traits, namely, plant stand, plant height, days to heading, days to maturity, tillers/meter, 1000-grain weight and grain yield. Analysis of variance revealed wide variability for most of the traits under study. The phenotypic coefficient of variation (PCV) was high for tillers/meter and grain yield, while high heritability coupled with high genetic advance were found for tillers/meter, 1000-grain weight and grain yield under all five environments. At phenotypic level, positive and significant correlation coefficients revealed that under all the normal and stressed environments used here, grain yield is directly influenced by plant stand, tillers/meter and thousand grain weights. Significant and positive correlations were estimated between tillers/meter (r = 0.31 to 0.66), and 1000 grain weight (r = 0.24 to 0.61) with grain yield under all five environments. Under waterlogged conditions there were significant negative correlations of plant height to grain yield (r = –0.38 to –0.39) across two sites. These results, thereby suggests that yield improvement in bread wheat could be possible by emphasizing these traits through selection in these diverse environments. On the basis of D2 values of pooled data, 108 genotypes were grouped into four clusters. In all, only 26 lines were found common in cluster III under two waterlogging environments (Faizabad and Karnal), while only 15 lines were common in cluster I under non waterlogging (Faizabad, CSSRI and DWR) conditions. These results indicate different constraints exist in waterlogged and non-waterlogged condition at these sites. Genetic diversity available for these traits may be utilized for yield improvement in bread wheat under different soil conditions through planned hybridization and selection in target environments.